Galvanostatic electrodeposition of Ni-Co alloys in DMSO under a magnetic field - Ebadi, M.; Mahmoudian, M.R.; Basirun, Wan Jefrey; Alias, Y. (2011)
This paper focuses on the galvanostatic magneto-electrodeposition of Ni-Co alloys in dimethyl sulphoxide (DMSO) in the presence and absence of a permanent parallel magnetic field (PPMF) to the cathode surface. It was found that the mass deposition was enhanced in the presence ofPPMF(9 T) compared with the deposition withoutPPMF. The percentage enhancement potential (ξ%) was elevated (ξ 5%=23.11, ξ 2%=10.65, ξ 0.5%= 4.85) with current densities of 5, 2 and 0.5mAcm -2, respectively, inthe presence of PPMF (9 T). Atomic force microscopy (AFM) showed that the roughness of the Ni-Co alloy films was reduced from 56.187 to 31.716nm(at 0.2mAcm -2) and 97.541 to 52.644nm(at 0.5mAcm -2) with appliedPPMF(9 T) compared with that without thePPMF. The deposited layers were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and energy dispersive X-ray analysis (EDX).